QUALITY MANAGEMENT IN THE ROMANIAN PHARMACEUTICAL FIELD DURING THE COVID-19 PANDEMIC - Calota-Toma, Binca; Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2022)
Health services are very important, as in any economy, because the life of all mankind depends on them. Bearing in mind that the pharmacist is the first and last filter in the medical system, we believe that they have a decisive role in the COVID-19 pandemic. Pharmacists must take extra measures to protect themselves, their families, and the community. All patients can be considered as COVID-positive, but pharmacists will offer them the same services and care as before. In the last 15 years, Romania has faced a complex socio-demographic process. The decrease in the birth rate, the general mortality rate and the emigration of the young population led both to the aging of the working age population and to the decrease of the total population of the country. All this aspect led to the reduction of the population size and required a rethinking of the health services system of social protection, in view of prolonging the active life of the population both from the point of view of the quality of the services offered and of the infrastructural facilities. The consumption of services represents an indicator of the quality of life, which we want to discuss in this article.